Tri-process model of interpersonal mindfulness: theoretical framework and study protocol - Khoury, Bassam; Manova, Viktoriya; Adel, Lena; Dumas, Guillaume; Lifshitz, Michael; Vergara, Rodrigo C.; Sekhon, Harmehr; Rej, Soham (Frontiers in Psychology, 2023)
According to the Center for Disease Control and Prevention, over 14% of the US population practice mindfulness meditation. The effects of mindfulness-training on physical and mental health have been consistently documented, but its effects on interpersonal relationships are not yet fully understood or investigated. Interpersonal relationships play a crucial role in the well-being of individuals and society. The aim of the proposed study is to investigate the interpersonal effects of mindfulness meditation training and the psychosocial mechanisms behind these effects. Using a multiphasic longitudinal design involving 640 participants randomized into 480 dyads, the proposed study will explore subjective self-reported experience and objective behavioral observation of the participants. Specifically, the proposed study will investigate how mindfulness meditation training impacts social emotional regulation, empathy, active empathic listening, social emotional support, compassion towards others, perspective taking, and mindful responding. In addition, the proposed study will investigate the indirect impacts of mindfulness meditation training on others’ emotional states. Therefore, the proposed research will extend the study of mindfulness from the intrapersonal to the interpersonal domain, specifically the impact of mindfulness training on the interpersonal interactions with others and their well-being. The proposed study has important academic and social implications and will allow devising new and more effective interpersonal mindfulness programs with applications in multiple fields, including parenting, teaching, counselling, management, physical and mental health, and intimate/conjugal relationships, among others.